Pengaruh Profesionalisme, Independensi, Kompetensi, dan Pengalaman Kerja Terhadap Kualitas Audit Pada Kantor Akuntan Publik Di Kota Medan - Wan Fachruddin; Yulia Syafriani Tjg (Jurnal Akuntansi Bisnis Eka Prasetya : Penelitian Ilmu Akuntansi, 2020)
This study aims to examine and analyze the effect of professionalism, independence, competence and work experience on audit quality. This study uses an associative approach. Population in this study are all auditors working at the Public Accountant Office (KAP) in Medan with a sample of 47 auditors . The sampling technique in this study uses convenience sampling techniques. The collection of data used in this study using a questionnaire. Data analysis techniques were performed with descriptive statistical analysis, multiple regression analysis test, classic assumption test, hypothesis test, and the coefficient of determination test and hypothesis testing with the help of SPSS version 16.0. The results of this study indicate that professionalism, competence and work experience have a significant effect on audit quality, independence does not significantly influence audit quality, and simultaneously professionalism, independence, competence, and work experience have an effect on audit quality. And based on the results of the coefficient of demination test can be seen that the value of the coefficient of demination of 0.594 means that the influence of professionalism, independence, competency, and work experience on audit quality is only 59.4%, the remaining 40.6% is influenced by other variables that are not used in this study.